Disentangling the binomial change/inertia to the Chilean educational policy in the post-dictatorship era (1990-2022). A normative policy instrument perspective - Villalobos, Cristóbal; Quiero-Bastías, Máximo; Pereira, Sebastián; Peralta, José (Journal of education policy, 2025)
Chile is a paradigmatic case of market-oriented educational policies. This has led to a prolific research agenda aimed at understanding the trajectory and trends during the country's dictatorial period and after the return to democracy. Generally, these studies have focused on comparing the main educational policies across different governments. In contrast, this article employs a normative policy instrument perspective to analyse the trajectory of Chilean educational policies from 1990 to 2022. The focus is on disentangling the inertia/change binomial in the implementation of educational policies, considering policy development within and between governments. Thus, the article seeks to understand when, how, and why subjects of educational policies, financial priorities, and ideological orientations change or persist over more than 30 years. The findings challenge the belief that educational policies are coherent and consistent within governments, identifying grey areas in each period. Additionally, the paper provides evidence of historical inertia in educational policies that transcends the ideologies of the governing parties. Finally, it is observed that changes in market-oriented educational policies have been more pronounced in the last decade, particularly during periods of political alternation between left- and right-wing governments.